2018
DOI: 10.1002/2017tc004738
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion of Magmatic Bodies Into the Continental Crust: 3‐D Numerical Models

Abstract: Magma intrusion is a major material transfer process in the Earth's continental crust. Yet the mechanical behavior of the intruding magma and its host are a matter of debate. In this study we present a series of numerical thermomechanical simulations on magma emplacement in 3‐D. Our results demonstrate the response of the continental crust to magma intrusion. We observe change in intrusion geometries between dikes, cone sheets, sills, plutons, ponds, funnels, finger‐shaped and stock‐like intrusions, and inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 87 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…Similarly, the higher density of intrusive mafic bodies, especially mafic and ultra‐mafic cumulates, would naturally lead to a signal in the gravity field as well as the change in seismic velocity (Richards et al., 2013; Ridley & Richards, 2010). We note that the high density of the mafic and ultramafic intrusions can lead to post‐emplacement deformation and downward crustal flow and potentially crustal delamination if the surrounding crust has sufficiently low viscosity (Gorczyk & Vogt, 2018; Roman & Jaupart, 2016, 2017). However, the presence of the upper crustal Bushveld complex (Eales & Cawthorn, 1996) and the lower crustal Seiland Igneous Province (R. Larsen et al., 2018) suggests that this process does not completely remove the crustal intrusives.…”
Section: Deccan Traps Intrusive Structure–geophysical Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the higher density of intrusive mafic bodies, especially mafic and ultra‐mafic cumulates, would naturally lead to a signal in the gravity field as well as the change in seismic velocity (Richards et al., 2013; Ridley & Richards, 2010). We note that the high density of the mafic and ultramafic intrusions can lead to post‐emplacement deformation and downward crustal flow and potentially crustal delamination if the surrounding crust has sufficiently low viscosity (Gorczyk & Vogt, 2018; Roman & Jaupart, 2016, 2017). However, the presence of the upper crustal Bushveld complex (Eales & Cawthorn, 1996) and the lower crustal Seiland Igneous Province (R. Larsen et al., 2018) suggests that this process does not completely remove the crustal intrusives.…”
Section: Deccan Traps Intrusive Structure–geophysical Observationsmentioning
confidence: 99%
“…We note that the common presence of a thick (∼5–15 km) underplated layer does not necessarily equate to a single magma body of equivalent size. Instead, frequent mafic intrusions(sills) at lower crustal depths along with visco‐elastic deformation of the cumulate bodies can also lead to the formation of a large seismic underplate layer (Galland et al., 2018; Gorczyk & Vogt, 2018; Roman & Jaupart, 2016, 2017; J. D. White et al., 2009). We have observational support for this hypothesis from an exhumed lower crustal LIP section ‐ the Seiland Igneous Province (SIP, R. Larsen et al., 2018, and references therein).…”
Section: Deccan Traps Intrusive Structure–geophysical Observationsmentioning
confidence: 99%
“…Such a design satisfies the generally acknowledged model, in which a relatively thin, vertical dyke acts as the fluid migration pathway and also the feeder of sands for conical sandstone intrusions Cartwright et al, 2008). This model has been adapted for several analogue and numerical modelling studies of sandstone and igneous intrusions (Mathieu et al, 2008;Galland et al, 2009;Bureau et al, 2014;Gorczyk and Vogt, 2018).…”
Section: Model Setupmentioning
confidence: 90%
“…Morgan and Chen 66 were the first to suggest that temperature was critical in controlling the depth of magma lenses at mid-ocean ridges. A recent three-dimensional numerical modeling study of magma intrusion into the continental crust indicates that rheology and temperature of the host rocks are the key controls of how magma is emplaced 67 . Parsons et al 68 first suggested that at large rheology contrasts where lower viscosity ductile layers are adjacent to a higher viscosity elastic layer, the least principal stress can be rotated vertically due to horizontal dike opening.…”
Section: Multi-sill Intrusion Modelmentioning
confidence: 99%